2006
DOI: 10.1111/j.1471-0528.2006.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and insulin resistance in early‐ and late‐onset pre‐eclampsia

Abstract: Objective To evaluate the importance of adiponectin and insulin resistance in early-and late-onset pre-eclampsia.Design A nested case-control study in 72 pregnant women who participated in the first-trimester Down-syndrome-screening programme and who delivered at our hospital.Setting University Hospital, Department of Obstetrics and Gynecology.Population Pregnant women: 36 women with pre-eclampsia of which 20 late onset and 16 early onset were compared with 36 uncomplicated pregnancies who delivered at term.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 31 publications
6
77
1
1
Order By: Relevance
“…Thus, our data suggest that elevation of circulating adiponectin may be a physiological response to the endothelial dysfunction caused by antiangiogenic factors derived from the placenta in late-onset PE, but not in early-onset PE. This is supported by the report by D'Anna et al 36 that first trimester adiponectin levels in late-onset PE are significantly lower than those in early-onset PE, suggesting that first trimester adiponectin values seem to differentiate two different populations: early-and late-onset PE. However, there were no differences in leptin levels between normal weight and Median (interquartile range).…”
Section: Discussionsupporting
confidence: 77%
“…Thus, our data suggest that elevation of circulating adiponectin may be a physiological response to the endothelial dysfunction caused by antiangiogenic factors derived from the placenta in late-onset PE, but not in early-onset PE. This is supported by the report by D'Anna et al 36 that first trimester adiponectin levels in late-onset PE are significantly lower than those in early-onset PE, suggesting that first trimester adiponectin values seem to differentiate two different populations: early-and late-onset PE. However, there were no differences in leptin levels between normal weight and Median (interquartile range).…”
Section: Discussionsupporting
confidence: 77%
“…The adipocytederived factor adiponectin, that is inversely related to insulin resistance and is low in women with obesity, is reduced in those who develop late-PE but not early-PE. 38 Similarly, increasing age is associated with glucose intolerance due to a reduction in insulin sensitivity 39 and abnormal lipid profile with increased triglycerides and cholesterol. 40 We found that Black women are at increased risk of early-PE and that both Black and South Asian women have increased risk for late-PE.…”
Section: Discussionmentioning
confidence: 99%
“…64 There is nonetheless strong evidence for the association of circulating hypoadiponectinemia during the first trimester with preeclampsia, compared with levels found in normal pregnancies. 65 This pattern is reversed in late pregnancy, as pre-eclampsia is associated with hyperadiponectinemia. 66 Other studies report that hypoadiponectinemia and preeclampsia correlate only when obesity 63 and gestational diabetes 67 are present as complicating factors.…”
Section: Effects Of Adiponectin On Reproduction and Fertilitymentioning
confidence: 99%